Effects of Polycyclic Aromatic Hydrocarbons on Soil Bacterial and Fungal Communities in Soils - Chunyong Wang; Haitao Wu; Weinong Zhao; Bo Zhu; Jiali Yang (Diversity)
Soil organic pollution (such as heavy metals, PAHs, etc.) has caused serious environmental problems, which have resulted in unexpected effects on contaminated soil ecosystems. However, knowledge of the interactions between environmental PAHs and bacterial and fungal communities is still limited. In this study, soil samples from different PAH-contaminated areas including non-contaminated areas (NC), low-contaminated areas (LC), and high-contaminated areas (HC) were selected. Results of toxic equivalent quantity (TEQ) indicated that Benzo[a]pyrene (BaP) and Dibenzo[a,h]anthracene (DBahA) constituted the main TEQs of ∑16PAHs. Incremental lifetime cancer risk (ILCR) assessment revealed that the main pathway of exposure to soil PAHs was dermal contact in adults and children. Furthermore, adults faced a higher total cancer risk (including dermal contact, ingestion, and inhalation) from soil PAHs than children. The microbial community composition analysis demonstrated that soil PAHs could decrease the diversity of bacterial and fungal communities. The relative abundance of Acidobacteriota, Gemmatimonadota, Fimicutes, Bacteroidota, Ascomycota, and Basidiomycota exhibited varying degrees of changes under different concentrations of PAHs. Benzo[a]anthracene (BaA) and Chrysene (Chr) drove the bacterial community composition, while BaP and DBahA drove the fungal community compositions. Co-occurrence network analysis revealed the high contamination levels of PAHs that could change the relationships among different microorganisms and reduce the complexity and stability of fungal and bacterial networks. Overall, these findings provide comprehensive insight into the responses of bacterial and fungal communities to PAHs.